« L’infamille ». Les violences familiales sur la céramique classique entre monstration et occultation - Aurélie Damet (Images Re-Vues)
Kinship ties are not easy to find on Greek vases. Only a mythological and often conflictual background, known by both the artist and the public, could provide clues to identify family members. Infanticide is particularly depicted and the violent and conscious mothers, as Medea, Prokne or Clytemnestra, are recurrent actors. Fathers could also kill their offspring but they appear in a menadic way, struck by madness sent by Dionysos (Herakles, Lycourgos). One must notice the rarity of the parricide and matricide as pictural motifs. Artists use two technical ways to show family conflicts on their productions. Medea is representative of the bloody and violent option. The subtle way is embodied by Alcmeon’s myth.